2009
DOI: 10.3855/jidc.66
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of drug resistance to phylogenetic groups of E. coli isolates from wound infections

Abstract: Background: Drug resistance is a major problem in Escherichia coli isolated from surgical wound infections. In this study, we evaluated relationship between phylogenicity and drug resistance. Methodology: A total of 29 multi-drug resistant (MDR) E. coli isolates of known drug resistance genes and integron profile were selected for the present study. Triplex PCR was conducted for phylogenetic classification of these isolates into four established phylogenetic groups: A, B1, B2 and D. Statistical analysis was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
(16 reference statements)
1
5
2
Order By: Relevance
“…In this study, group A had the lowest prevalence. This result is in contrast to those noted in some previous studies of extraintestinal E. coli which indicated that most of isolates belonged to group A [ 15 , 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, group A had the lowest prevalence. This result is in contrast to those noted in some previous studies of extraintestinal E. coli which indicated that most of isolates belonged to group A [ 15 , 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This result was in accordance with other studies [35,36]. The results of two independent studies conducted by Saeed and Dadie indicated that most of the isolates belonged to group A, which is in contrast to our study [37,38]. This difference in the phylogroup distribution can be due to several factors such as genetic, dietary, health, environmental and geographic conditions of the host [39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…In case of E. coli, 39% were found to be MDR, which is in accordance with the previous reports where 33.9% and 34.19% MDR were observed from clinical specimens. 19,20 Prevalence of MDR in K. pneumoniae was found to be 45%, which is much higher than 22.5% reported recently from Karachi. 20 This difference could be due to the low number of K. pneumoniae isolates in both studies.…”
contrasting
confidence: 51%